Supply Chain Network Design integrating Economic, Risk and Energy Sustainability - Reihaneh Naderi; Mohsen Shafiei Nikabadi; Akbar Alem Tabriz; Mir Saman Pishvaee (Environmental Energy and Economic Research)
Supply chains and economic systems have an important role in environmental issues and energy sustainability. Energy is a key factor of all economic systems and has a large environmental impact, therefore its affordable consumption is very important to have a sustainable supply chains and sustainable future. This paper provides a new formulation of supply chain network design by integration of thermodynamic rules about available or useful energy and econometric coefficients and also risk factor in supply chain. The purpose of this integration is to achieve a sustainable supply chain modeling in both fields of available energy and total costs that can guarantees both return of the investments and useful energy in the economic systems. In order to solve the proposed model, augmented ε-constraint method is used and numerical examples are discussed and the results illustrate that the proposed model admitted various progresses in minimizing consumed available energy along with the total costs and risk factor in the proposed model. Also results show that the Gross Domestic Product (GDP) and two of the econometric coefficients generally pointed out as “alpha” and “beta” play a significant role in the amount of consumed available energy and energy sustainability in the supply chain.